2018
DOI: 10.1248/cpb.c17-00800
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Compounds from Ansamycin Antibiotic Class as Inhibitors of PD1–PDL1 Protein–Protein Interaction

Abstract: The ability of tumors to escape from immune destruction is attributed to the protein-protein interaction between programmed cell death protein 1 (PD1) and programmed cell death ligand 1 (PDL1) proteins expressed by immune T cells and cancer cells, respectively. Therefore, pharmacological inhibition of the PD1-PDL1 interaction presents an important therapeutic target against a variety of tumors expressing PDL1 on their cell surface. Recently, five antibodies have been approved and several are in clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This may provide an alternative scaffold and extra fragments for the design of new small-molecule antagonists of the PD-1/PD-L1 pathway [38,39,44] (See also Section 2.2, Figure 17). For example, an interesting application of the MCPs as potential inhibitors of PD-L1 was proposed by Patil et al [45] who showed that macrocyclic compounds 5 and 6 from the ansamycin class of antibiotics are capable to inhibit the PD-1/PD-L1 interaction (Figure 4).…”
Section: Inhibitors Of the Pd-1/pd-l1 Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may provide an alternative scaffold and extra fragments for the design of new small-molecule antagonists of the PD-1/PD-L1 pathway [38,39,44] (See also Section 2.2, Figure 17). For example, an interesting application of the MCPs as potential inhibitors of PD-L1 was proposed by Patil et al [45] who showed that macrocyclic compounds 5 and 6 from the ansamycin class of antibiotics are capable to inhibit the PD-1/PD-L1 interaction (Figure 4).…”
Section: Inhibitors Of the Pd-1/pd-l1 Interactionmentioning
confidence: 99%
“…A particularly good result was obtained for 6 that showed an IC 50 of approximately 25 µM. This led the authors to conclude that such macrocycles could become an inspiration for the development and optimization of a potent and truly small-molecule antagonist of the PD-1/PD-L1 interaction [45].…”
Section: Inhibitors Of the Pd-1/pd-l1 Interactionmentioning
confidence: 99%
“…Recently, Zak et al revealed the molecular features of the human PD-1/PD-L1 interaction based on the X-ray structure of the complex, and several hot spots located on the PD-L1 molecule were shown to be involved in the formation of the complex (15,30). To date, several small molecules, macrocyclic peptides and peptide mimetics targeting the PD-1/PD-L1 interaction have been reported (8,18,19), primarily in patent applications, but almost no fully validated and qualified therapeutics exist. Recently, the binding action and biological activities of potent small molecule inhibitors of PD-1/PD-L1 have been reported by Bristol-Myers Squibb (BMS) (1,31,32).…”
Section: Development Of Humanized Nog-dko Mice Six-mentioning
confidence: 99%
“…[7] As a result, different alternative therapeutics that are much smaller than these mAbs are currently being explored to target the binding interfaces on both the PD-1 and PD-L1 receptors. These include small PD-1 protein fragments [8] and macrocyclic peptides, [9,10] many of which showed significantly better activity than the larger mAbs. These peptides and peptidomimetics thus can provide a good starting point in designing and optimizing the potent, truly small-molecule antagonists of the PD-1/PD-L1 interaction.…”
mentioning
confidence: 99%